Risk Based Acceptance Criteria for Joints Subject to Fatigue Deterioration - Straub, Daniel; Faber, Michael H. (Journal of Offshore Mechanics and Arctic Engineering, 2005)
ISSN:0892-7219 ISSN:1528-896X